Urinary stones in a continent catheterizable pouch: A case report (Indian Journal of Case Reports, 2020)
Changes in anatomy, as well as other metabolic factors, often result in the urinary tract infection and urolithiasis in patients after urinary diversion. The surgical management of stones in patients after urinary diversion is challenging. We report the case of a 21-year-old female presenting with fever. This patient had earlier undergone the creation of a continent urinary reservoir with appendicular catheterizable stoma for a failed exstrophy repair. We report the management of urinary stones occurring in this patient.